An application of Catholic symbolism featuring Blessed Chiara Badano, Blessed Pier Giorgio Frassati, and Saint Teresa of Calcutta - Harmon, Caroline, author (Colorado State University. Libraries, 2024)
This paper explores Catholic symbolism as it relates to the portraits I have created of three remarkable individuals: Blessed Chiara "Luce" Badano, Blessed Pier Giorgio Frassati, and Saint Teresa of Calcutta. It opens with a broad discussion of the historical relationship between art and the Catholic Church, tracing how artistic expression has been intrinsically linked to the faith since its inception. This examination encompasses the use of visual arts in liturgy, the role of artists as conveyors of theological concepts, and the way sacred imagery can shape the spiritual lives of churchgoers. Following this historical context, the paper presents concise and detailed biographies of the three figures. It delves into the lives of Chiara, Pier Giorgio, and Teresa, highlighting their backgrounds, key life events, and the defining moments that led them to be recognized as models of holiness. For instance, it discusses Chiara's vibrant faith in her battle with illness, Pier Giorgio's enthusiastic commitment to social justice and outreach, and Teresa's profound dedication to the poorest of the poor. The analysis continues by examining how the symbols depicted in the portraits of these holy individuals—such as a grapevine and wheat, flowers, and a cross-anchor—reflect their values and spiritual journeys. Ultimately, this work highlights the profound connection between art and the Catholic faith and the lived experiences of these three saints, illustrating how their stories continue to resonate within the Catholic community today.
University Honors Program, College of Veterinary Medicine and Biomedical Sciences, Colorado State University. HONR499: Honors Thesis, Advisor: Dr. Joel Bacon, Committee Member: Dr. Catherine DiCesare. Fall 2024.
Keywords: Catholic church; Badano, Chiara; Frassati, Pier Giorgio; Teresa of Calcutta; symbolism; art; art history